Moderate alcohol use and reduced mortality risk: systematic error in prospective studies. - Fillmore, K.; Kerr, W.; Stockwell, Tim; Chikritzhs, Tanya; Bostrum, A. (Informa Healthcare, 2006)
The majority of prospective studies on alcohol use and mortality risk indicates that abstainers are at increased risk of mortality from both all causes and coronary heart disease (CHD). This meta-analysis of 54 published studies tested the extent to which a systematic misclassification error was committed by including as 'abstainers' many people who had reduced or stopped drinking, a phenomenon associated with ageing and ill health. The studies judged to be error free found no significant all-cause or cardiac protection, suggesting that the cardiac protection afforded by alcohol may have been over-estimated. Estimates of mortality from heavier drinking may also be higher than previously estimated.